2013
DOI: 10.1371/journal.pone.0080084
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Role of the Small Leucine-Rich Proteoglycan Biglycan in Bladder Cancer

Abstract: BackgroundUrothelial bladder cancer is the ninth most common cancer. Despite surgical and chemotherapeutic treatment the prognosis is still poor once bladder cancer progresses to a muscle-invasive state. Discovery of new diagnostic markers and pathophysiologic effectors might help to contribute to novel diagnostic and therapeutic options. The extracellular matrix microenvironment shaped by the extracellular matrix critically affects tumor cell and stroma cell functions. Therefore, aim of the present study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 52 publications
4
38
0
Order By: Relevance
“…However, the best survival rate was displayed in human bladder cancer with high BGN gene level. The in vivo and in vitro experiment that knockdown BGN enhanced the proliferation ability of bladder cancer cells was agreed with the results, indicating that BGN may be a growth suppressor in human bladder cancer [16]. To our knowledge of inflammation effects on tumorigenesis, it suggests that BGN, similar to decorin, might inhibit tumor growth of established tumors by creating the TLR2/4-mediated proinflammatory environment.…”
Section: Discussionsupporting
confidence: 78%
“…However, the best survival rate was displayed in human bladder cancer with high BGN gene level. The in vivo and in vitro experiment that knockdown BGN enhanced the proliferation ability of bladder cancer cells was agreed with the results, indicating that BGN may be a growth suppressor in human bladder cancer [16]. To our knowledge of inflammation effects on tumorigenesis, it suggests that BGN, similar to decorin, might inhibit tumor growth of established tumors by creating the TLR2/4-mediated proinflammatory environment.…”
Section: Discussionsupporting
confidence: 78%
“…35 In cancer, seemingly contradicting data have revealed that increased BGN expression is linked with poor prognosis, 36 whereas its overexpression was associated with inhibition of cancer cell growth. 37,38 We investigated the loss of BGN in the absence of TAp73 (W1 cells) and revealed that Bgn expression was drastically reduced in TAp73-deficient cells compared with that in 4A cells as well as in Panc1 cells transfected with TAp73 siRNA compared with that in Panc1 cells transfected with siCtr (Figure 4d). This suggests that Bgn, which has seven response elements for p53 family proteins according to the p53FamTaG database, 39 could be a direct transcriptional target of TAp73.…”
Section: Resultsmentioning
confidence: 99%
“…This finding was also supported by showing a significantly higher immunostaining for Biglycan in ESCC. A single study by Niedworok et al 45 in urinary bladder cancer had demonstrated an increase in Biglycan expression at mRNA level as well as at protein level by IHC. Thus, our results on Biglycan expression are also in accordance with the previous studies.…”
Section: Discussionmentioning
confidence: 99%